Haemophilic magnetic resonance imaging score in healthy controls playing sports. (28th May 2013) - Foppen, W.; Sluiter, D.; Witkamp, T. D.; Mali, W. P. T. M.; Fischer, K.
Summary: Magnetic resonance imaging (MRI) is the most sensitive imaging modality to assess joint lesions, but the clinical relevance of subtle joint changes in haemophilic patients playing sports is unknown. A haemophilia specific MRI score is available, but was never evaluated in physically active healthy controls. It is not known if unexpected MRI changes in young active haemophilic patients are due to sports participation. The aim of this study was to evaluate knees and ankles in a cohort of young active healthy men using a haemophilia specific MRI score to provide context for joint evaluation by MRI in young haemophilic patients. Three Tesla MRI of knees and ankles were performed in 30 healthy men aged 18–26 years, regularly active in sports. MR images were scored by a single independent radiologist, using the International Prophylaxis Study Group additive MRI score. One physiotherapist assessed clinical function using the Haemophilia joint health scores (HJHS). History of complaints or injuries affecting knees and/or ankles, very intensive sports and current sports activities were documented. Median age was 24.3 years (range 19.0–26.4) and median number of sports activities per week was 3 (range 1–4). Six joints (five knees, one ankle) had a history of a sports‐related injury. The median HJHS per joint was 0 out of 20 (range 0–1). All joints had a MRI score of 0. These results suggest that regular sports participation or very low HJHS scores are not associated with haemophilia specific MRI changes in knees and ankles.